2005
DOI: 10.1002/art.21144
|View full text |Cite
|
Sign up to set email alerts
|

Angiography‐negative primary central nervous system vasculitis in children: A newly recognized inflammatory central nervous system disease

Abstract: Inflammatory central nervous system (CNS) diseases in childhood comprise a wide spectrum of heterogeneous conditions. We studied 4 children with primary CNS vasculitis in whom results of magnetic resonance imaging studies were abnormal but results of conventional angiography were normal. We determined that angiography-negative, biopsy-confirmed primary smallvessel CNS vasculitis is a previously unrecognized distinct disease entity in children. The diagnosis must be considered in a child with a progressive, acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
110
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 143 publications
(123 citation statements)
references
References 23 publications
6
110
1
5
Order By: Relevance
“…However, isolated small-sized vessel PCNSV involves a subgroup of patients in whom DSA findings (and a fortiori 3D-TOF-MRA) are also mostly negative, and only biopsy can show vascular involvement in these patients. 9,[20][21][22] In our first description of the French cohort, as well as in another large study by Salvarani et al, 23 twothirds of the patients with biopsy-proved PCNSV had negative DSA findings. 9 In the present study, 6 of our 7 patients with isolated small-sized vessel vasculitis demonstrated by biopsy had normal 3D-TOF-MRA and DSA findings.…”
mentioning
confidence: 61%
“…However, isolated small-sized vessel PCNSV involves a subgroup of patients in whom DSA findings (and a fortiori 3D-TOF-MRA) are also mostly negative, and only biopsy can show vascular involvement in these patients. 9,[20][21][22] In our first description of the French cohort, as well as in another large study by Salvarani et al, 23 twothirds of the patients with biopsy-proved PCNSV had negative DSA findings. 9 In the present study, 6 of our 7 patients with isolated small-sized vessel vasculitis demonstrated by biopsy had normal 3D-TOF-MRA and DSA findings.…”
mentioning
confidence: 61%
“…Distinct subtypes have been identified based on the vessel size involved and course of inflammatory illness [5,6]. Largemedium vessel cPACNS or angiography-positive cPACNS is an inflammatory vascular disease that can affect the intracranial internal carotid arteries (ICA), the circle of Willis and its branches, the posterior cerebral circulation, and the spinal vessels up to the resolution of 3-T magnetic resonance angiography and/or conventional angiography [5,9].…”
Section: Childhood Primary Cns Vasculitismentioning
confidence: 99%
“…This definition excludes small muscular arteries, arterioles, capillaries and venules, which are considered "small vessels of the brain." Therefore, by definition, small vessel cPACNS is an angiography-negative inflammatory brain disease [6]. Within a cerebral vessel, the distinction of proximal segments-defined as the first-and second-order branches-and distal segments-defined as any segments beyond second branching-is commonly made.…”
Section: Childhood Primary Cns Vasculitismentioning
confidence: 99%
See 2 more Smart Citations